2022
DOI: 10.5935/1984-0063.20220080
|View full text |Cite
|
Sign up to set email alerts
|

Possible etiologies of restless legs syndrome in pregnancy: a narrative review

Abstract: Restless legs syndrome (RLS) is a sensorimotor disorder characterized by an urgent need to move the legs, due to the presence of a discomfort sensation in the lower limbs, especially at rest. Generally, it relieves with movement. There are several studies that argue the existence of an association between this syndrome and pregnancy. However, the pathophysiological mechanisms of this disorder in pregnancy are misunderstood. The objective of this narrative review is to identify and discuss some possible etiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(162 reference statements)
2
5
0
Order By: Relevance
“…RLS prevalence during pregnancy in different countries has been reported at a range of 13.5-34%, in line with our findings [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. According to Turkish studies, the prevalence of RLS during pregnancy ranges from 15.4% to 61.2% [5][6][7][8][9]11,12].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…RLS prevalence during pregnancy in different countries has been reported at a range of 13.5-34%, in line with our findings [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. According to Turkish studies, the prevalence of RLS during pregnancy ranges from 15.4% to 61.2% [5][6][7][8][9]11,12].…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies have shown that iron plays a role in the etiopathogenesis of RLS [19,27]. Iron, ferritin, and serum folate levels drop during pregnancy, as does hemoglobin, another iron indication [1,28]. There is evidence that the number of pregnancies can affect iron levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Present understanding also highlights a strong role of family history in RLS occurrence [30]. In the already mentioned study RLS appeared in 11,4% of women without RLS in the family and in 74,2% pregnant women with family history of this disorder.…”
Section: Restless Leg Syndromesupporting
confidence: 62%
“…In the general population, a high prevalence of RLS was reported (up to 10%) [ 4 ], RLS being more commonly encountered in females [ 5 ]. Secondary causes of RLS have also been identified: renal failure [ 6 ], hepatic cirrhosis [ 7 ] and pregnancy (generally with a tendency to decrease after delivery) [ 8 ]. On the other hand, RLS can be encountered in other less-common conditions, such as rheumatoid arthritis [ 9 ], fibromyalgia [ 10 ], multiple sclerosis [ 11 ] or systemic lupus erythematosus [ 12 ].…”
Section: Introductionmentioning
confidence: 99%